FIBER FRACTION OF CABBAGE AND MUSTARD VEGETABLE WASTE SILAGE USING VARIOUS ADDITIVE SOURCES - Harahap, Anwar Efendi; Adelina, Triani; Handoko, Jully; Permatasari, Diah Ayu (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2024)
Utilization of cabbage and mustard waste as an alternative to forage for livestock is one of the efforts in providing limited forage in the dry season in the form of silage. Additives can be added to improve the quality of the silage. This study aims to determine the quality of the fiber fraction contained in the silage of cabbage and mustard waste using a variety of different additive sources. This study used a completely randomized design (CRD) with 4 treatments and 5 replications. The treatments were, P1 (70% cabbage and mustard waste + 30% rice bran); P2 (70% cabbage and mustard waste + 30% corn flour); P3 (70% cabbage and mustard waste + 30% tapioca starch waste); P4 (70% cabbage and mustard waste + (30% rice bran + corn flour + tapioca starch waste)). Parameters observed included NDF, ADF, ADL, cellulose and hemicellulose content. The results of this study showed that the administration of different additives had a very significant effect (P<0.01) on decreasing the content of NDF, ADF and ADL, having a significant effect (P<0.05) on increasing the cellulose and hemicellulose content it conclude that the use of various additive sources reduces the content of NDF, ADF, and ADL and increase the content of hemicellulose and cellulose silage made from cabbage and mustard waste.